MVA as a vector for vaccines against HIV-1. - Im, E; Hanke, T (2004)
A vaccine against HIV Type 1 (HIV-1) is urgently needed. Modified vaccinia virus Ankara is an attenuated smallpox vaccine which can be adapted to express HIV-1 antigens. In this review, we discuss the features which make modified vaccinia virus Ankara an attractive vector for genetic vaccines and have put it, together with several other recombinant viral vectors, at the forefront of HIV-1 vaccine development. Many candidate vaccines including those vectored by modified vaccinia virus Ankara are now entering human trials, the results of which will become available in the coming years.